The Development of HOTS Questions Based on Ethnomathematics to Measure Students' Mathematical Problem-Solving Abilities - Sinar Depi Harahap; Marzuki Ahmad; Joni Winra Pasaribu (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
The research aims to develop ethnomathematics-based Higher Order Thinking Skills (HOTS) questions to measure students' problem-solving abilities. This research uses a research and development (R&D) method with an ADDIE model, which consists of five stages, i.e., analysis, design, development, implementation, and evaluation. The subjects in this research were 30 class VIII students at SMP Negeri 1 West Sorkam. Research instruments include expert validation questionnaires, student response questionnaires and tests of students' mathematical problem-solving abilities. The research data were analyzed using quantitative descriptive methods by determining the average achievement value of the products developed. The experts' assessment shows that the product developed has a score of 84.6 with the criteria "Very Valid". Based on the results of the questionnaire, students' responses to HOTS questions based on ethnomathematics were seen from the practical aspect with a score of 77.63 in the "Practical" criteria and the results of tests on students' mathematical problem-solving abilities obtained an average score of 75.22 so that the product developed met the "effective" criteria. So it can be concluded that the development of ethnomathematics-based HOTS questions on geometric material produces a good product and is suitable for measuring students' mathematical problem-solving abilities.